Evaluating the efficacy of small molecules for neural differentiation of common marmoset ESCs and iPSCs. (June 2020) - Yoshimatsu, Sho; Nakamura, Mari; Nakajima, Mayutaka; Nemoto, Akisa; Sato, Tsukika; Sasaki, Erika; Shiozawa, Seiji; Okano, Hideyuki
Highlights: Chemical treatment enhanced the neural differentiation capacity of marmoset PSCs. NEUROG2 overexpression resulted in nearly 100% neuronal induction from cjESCs. Enriched neuronal/glial gene expression in differentiated cells with the EB method. Enriched neuronal gene expression in differentiated cells with the iN method. ZFP521 gene may involve in the neural differentiation propensity of marmoset PSCs. Abstract: The common marmoset (marmoset; Callithrix jacchus ) harbors various desired features as a non-human primate (NHP) model for neuroscience research. Recently, efforts have been made to induce neural cells in vitro from marmoset pluripotent stem cells (PSCs), including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), which are characterized by their capacity to differentiate into all cell types from the three germ layers. Successful generation of marmoset neural cells is not only invaluable for understanding neural development and for modeling neurodegenerative and psychiatric disorders, but is also necessary for the phenotypic screening of genetically-modified marmosets. However, differences in the differentiation propensity among PSC lines hamper the applicability and the reproducibility of differentiation methods. To overcome this limitation, we evaluated the efficacy of small molecules for neural differentiation of marmoset ESCs (cjESCs) and iPSCs using multiple differentiation methods. By immunochemical and transcriptomic analyses, we confirmed that our methods using the small molecules are efficient for various differentiation protocols by either enhancing the yield of a mixture of neural cells including both neurons and glial cells, or a pure population of neurons. Collectively, our findings optimized in vitro neural differentiation methods for marmoset PSCs, which would ultimately help enhance the utility of the animal model in neuroscience.